Relevant legal bases in the processing of personal data in the contracts of digital contents and digital services - García Pérez, Rosa María (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The European process of revision, modernization and adaptation of consumer protection rules to the technological environment has brought into contact two regulatory spheres of opposite interests: personal data protection and consumer law. The first inflection point of the complex interaction between both regulatory frameworks has come from the hand of Directive (EU) 2019/770 of the European Parliament and of the Council, of 20 May 2019, on certain aspects concerning contracts for the supply of digital content and digital services, which offers the same contractual remedies both to consumers who pay a price and to those who, by way of counter performance, provide their personal data. Of the new and interesting perspectives of analysis offered by the overlapping of the fundamental right to data protection in the contractual sphere, this paper focuses on the determination of the bases of lawfulness, according to the General Data Protection Regulation, of the processing of derived personal data of the scope of the Directive and its contractual impact.
Keywords: EU Digital Single Market; interaction consumer law - data protection regulation; supply of digital content and digital services; counter-performance in the form of personal data; principle of lawfulness of the personal data processing